The Role of Religion in Social and Democratic System Justification: The Case of Italian Catholicism - Rutto, Filippo; Viola, Erica; Monaci, Maria Grazia (Journal for the Academic Study of Religion, 2021)
The aim of the current study is to explore, within the Italian Catholic context, the impact of scriptural literalism and religious orientation on the ideologies that legitimate the social and the democratic system. A sample of Catholic participants completed an anonymous self-report questionnaire concerning: a) scriptural literalism; b) intrinsic and extrinsic religious orientation; c) social and democratic system justification. Results show that scriptural literalism affects both intrinsic and extrinsic religious orientation, with extrinsic, but not intrinsic orientation tending to increase both social and democratic system justification. These results extend previous findings on the relationship between religion and the legitimisation of the social system. Possible implications for increasing social fairness in the future, filling the gap between religious precepts and an unconditional acceptance of social order, are also discussed.